Educational Robotics as an Effective Use of Technology to Enhance Learning - Abu Mukh, Yasmeen Nzam (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Many studies provide that students who learn through participation technology, while participating in the educational process, especially in magic robot programs, make decisions in a magical way (at least this is what some students think before they know about programming and sensors) It attracts students and picks them up, and this It is the reason why they are busy with technology-enhanced learning inside warfare, with a special focus on educational robot programs [6] , and it should be noted that some research highlights that some valuable comments and ideas will not only inspire future exploration in this field, but also To reassess critical evaluation of programs that may not live up to your ideal.